2021
DOI: 10.3389/fncel.2021.725267
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Alleviates Microglia-Induced Spinal Inflammation and Hyperalgesia in Neonatal Rats by Systemic Lipopolysaccharide Exposure

Abstract: Noxious stimulus and painful experience in early life can induce cognitive deficits and abnormal pain sensitivity. As a major component of the outer membrane of gram-negative bacteria, lipopolysaccharide (LPS) injection mimics clinical symptoms of bacterial infections. Spinal microglial activation and the production of pro-inflammatory cytokines have been implicated in the pathogenesis of LPS-induced hyperalgesia in neonatal rats. Dexmedetomidine (DEX) possesses potent anti-neuroinflammatory and neuroprotectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 62 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…In a recent study, effects of Dex have been shown to attenuate pro-inflammatory response and exhibit neuroprotection in spinal cord ischemia. Moreover, Dex can increase microglia-associated anti-inflammatory cytokines levels [12]. However, the effect of using miR-30a-5p in combination with Dex on microglia with inflammatory response was not confirmed.…”
Section: Introductionmentioning
confidence: 92%
“…In a recent study, effects of Dex have been shown to attenuate pro-inflammatory response and exhibit neuroprotection in spinal cord ischemia. Moreover, Dex can increase microglia-associated anti-inflammatory cytokines levels [12]. However, the effect of using miR-30a-5p in combination with Dex on microglia with inflammatory response was not confirmed.…”
Section: Introductionmentioning
confidence: 92%